Lectin from Agaricus Bisporus Suppresses Akt Phosphorylation and Arrests Cell Cycle Progression in Primary Human Retinal Pigment Epithelial Cells - Y. H. Cheung; D Wong; A. C. Y. Lo; W. W. K. Lai (i-Perception, 2011)
Anomalous retinal pigment epithelial (RPE) cells have been implicated in the development of retinal diseases. Lectin from the edible mushroom Agaricus bisporus (ABL) was found to inhibit growth of RPE cells. To elucidate the mechanism through which ABL inhibits RPE cell proliferation, we investigated the changes in cell proliferation-related signaling pathways and cell cycle distribution patterns. Primary human RPE cells were grown with or without the lectin (ABL) supplement (20ug or 90ug/ml) for three days. Phosphorylation statuses of Akt, Jnk and p38 as well as p53 expression level were investigated by Western blotting. Cellular distributions in various cell cycle phases were investigated using flow cytometry. After ABL treatment (90ug/ml), Akt was found to be hypo-phosphorylated while the expression levels of p53, phosphorylated-Jnk and phosphorylated-p38 were not altered. The amount of cells present at S phase was reduced. Our results showed that ABL hypo-phosphorylated Akt and this observation is in line with the finding that ABL could attenuate cell proliferation. As the level of p53 was not significantly altered by ABL, this suggested that the mechanism in which ABL arrested cell proliferation was independent of Akt-mediated MDM2 activation but was possibly mediated by altering G1 to S phase transition.